Building Loyalty through Trust: The Role of Sharia Compliance, Satisfaction, and Service Quality at Muhammadiyah Amanah Sumpiuh Hospital - Hernandes, Crodia; Riptiono, Sulis (Jurnal Economic Resource, 2025)
This study aims to analyze the influence of Hospital Syariah Compliance, Patient Satisfaction, and Service Quality on Patient Loyalty, with Patient Trust as a mediating variable. The background of this study is based on the importance of integrating Islamic values in healthcare services to build long-term relationships with patients, especially in sharia-based hospitals. The study was conducted at Muhammadiyah Amanah Sumpiuh Hospital involving 263 patient respondents who had received services at least twice. The method used is a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis using SmartPLS-4 software. The results show that Hospital Syariah Compliance, Patient Satisfaction, and Service Quality have a significant effect on Patient Loyalty, both directly and indirectly through Patient Trust. Trust is proven to mediate the relationship between the three exogenous variables on loyalty, with full mediation on the relationship between service quality and sharia compliance on loyalty, and partial mediation on the path of satisfaction on loyalty. The conclusion of this study confirms that trust is a key element in shaping patient loyalty, especially in the context of hospitals based on Islamic values.